Characterization of Klebsiella pneumoniae complex isolates from pigs and humans in farms in Thailand: population genomic structure, antibiotic resistance and virulence genes. (8th April 2021) - Leangapichart, Thongpan; Lunha, Kamonwan; Jiwakanon, Jatesada; Angkititrakul, Sunpetch; Järhult, Josef D; Magnusson, Ulf; Sunde, Marianne
Abstract: Objectives: To define characteristics of Klebsiella pneumoniae complex (hereafter KP) isolates from healthy pigs, farm workers and their household members in Thailand. Methods: A total of 839 individual rectal swabs from pigs on 164 farms and 271 faecal samples of humans working on pig farms and persons living in the same household in Khon Kaen, Thailand were screened for gut colonization by KP. Genomic sequences were investigated for antibiotic resistance and virulence genes. Phylogenetic analyses were performed in addition to comparison with isolates from previous studies from Thailand. Results: KP was detected in approximately 50% of pig and human samples. In total, 253 KP isolates were obtained: 39% from pigs, 34% from farmers and 26% from individuals living on the same farm but without animal contact. MLST revealed high genetic diversity with 196 different STs distributed over four phylogroups (Kp1 to Kp4). Low prevalence of ESBL-KP (7.5%) and colistin-resistant KP (3.2%) was observed among pigs and humans. Remarkably, four convergent MDR and hypervirulent strains were observed: one from pigs (ST290) and three from humans [ST35, ST3415 (strain 90CP1), ST17 (strain 90CM2)]. Sharing of KP clones among pigs and humans was identified for some STs including ST4788, ST661, ST3541 and ST29. Conclusions: The study indicated a low prevalence of ESBL and mcr genes among KP isolated from pigs and healthy humans in Thailand and suggested the possibility of zoonotic transmission for a subset of circulating KP clones.